2005
DOI: 10.1177/153331750502000103
|View full text |Cite
|
Sign up to set email alerts
|

Integrated treatment approach improves cognitive function in demented and clinically depressed patients

Abstract: The purpose of this study was to evaluate the efficacy of an integrative treatment approach on cognitive performance. The study sample comprised 35 medically ill patients (20 male, 15 female) with an average age of 71.05, who were diagnosed with mild dementia and depression. These patients were evaluated at baseline and at six, 12, and 24 months of treatment, which included antidepressants (sertraline, citalopram, or venlafaxine XR, alone or in combination with bupropion XR), cholinesterase inhibitors (donepez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 16 publications
3
56
0
4
Order By: Relevance
“…Inhibition of cytochrome P-450 by some antidepressants, such as paroxetine [37] , may indeed increase plasma levels of cholinergic drugs. Moreover, serotoninergic and cholinergic drugs might act synergistically to improve cognitive function, as observed in preclinical models [38,39] and suggested by preliminary clinical studies of AD patients [40] . Hence, randomized clinical trials aiming at evaluating the effect of this association would be welcome.…”
Section: Discussionmentioning
confidence: 92%
“…Inhibition of cytochrome P-450 by some antidepressants, such as paroxetine [37] , may indeed increase plasma levels of cholinergic drugs. Moreover, serotoninergic and cholinergic drugs might act synergistically to improve cognitive function, as observed in preclinical models [38,39] and suggested by preliminary clinical studies of AD patients [40] . Hence, randomized clinical trials aiming at evaluating the effect of this association would be welcome.…”
Section: Discussionmentioning
confidence: 92%
“…Besides, in later studies an improvement in patients' ability to perform daily activities has also been reported [8] . Fewer studies have evaluated the efficacy of other interventions such as neuropsychological rehabilitation [9] , physical exercises [10] , or a combination of pharmacological and nonpharmacological treatments [11] . Some researchers have confirmed that cognitive stimulation in elderly people reinforces the effect of pharmacological treatment to the same extent in both communication and functional abilities [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many research studies [32][33] call for a multidisciplinary team treatment approach to TBI, which would include medical professionals (eg, psychiatrist, neurologist, or psychologists), social workers, rehabilitation specialists, and speech therapists. Moreover, specialist medical professionals emphasize a benefit of the socalled integrated treatment approach of antidepres sants, cholinesterase inhibitors, vitamins, diet, healthy lifestyle, and physical activities, which may have a positive effect on cognitive functioning [34]. Lately, there has also been a rise in using assistive technologies such as telemedicine in military TBI which can remotely connect patients with their doctor specialists; provide prescriptions online; provide realtime video visits with family members; or receive information about health [35].…”
Section: Discussionmentioning
confidence: 99%